The Influence of Investments, Education, Health, Labor Force Participation Rate, and Covid-19 Pandemic on Poverty In Java for the 2013-2023 Period - Damayanti, Silmi Annisa; Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Java Island continues to face high poverty levels, with 13.62 million people living in poverty in 2023. This study analyzes the effects of investment, education, health, the Labor Force Participation Rate (LFPR), and the Covid-19 pandemic on poverty in six provinces of Java during 2013–2023 using panel data regression with the Fixed Effect Model (FEM) and robust standard errors. The results show that education and LFPR have a negative and significant effect on poverty, while health has a positive and significant effect. Investment has a negative but insignificant effect, indicating unequal distribution. The Covid-19 pandemic significantly increased poverty levels. These findings highlight that poverty alleviation policies should focus on improving education quality, expanding employment opportunities, ensuring more equitable investment distribution, and strengthening inclusive health services. In addition, adaptive social protection systems are required to anticipate external shocks such as pandemics.